Clinical characteristics and predictive factors of refractory Mycoplasma pneumoniae pneumonia - Liu, Jin-rong (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2012)
OBJECTIVE: To investigate clinical characteristics and predictive factors of refractory Mycoplasma pneumoniae pneumonia (RMPP) in children so as to recognize and treat the disease earlier